Can handheld ultrasound probes reliably measure transabdominal prostate and bladder volumes? A prospective randomized point-of-care ultrasound study - Wright, Henry C.; Corrigan, Dillon; De, Smita (Frontiers in Urology, 2025)
BackgroundNational guidelines recommend obtaining prostate gland volume (PGV) prior to benign prostate hyperplasia (BPH) surgery. Measurement of PGV with handheld ultrasound (HUS) probes shows promise.ObjectiveTo compare the reliability of two HUS probes (Butterfly iQ and Clarius C3) to the BPH guideline-recommended imaging (GIm) for both prostate and bladder volumetrics.MethodsMale patients with GIm were randomized to undergo transabdominal HUS PGV with one of the two probes. A subset underwent voided volume measurements with one of the two HUS and a conventional bladder scanner (BS). The reliability of the volume measurements was assessed for each probe via intraclass correlation coefficients (ICCs). We utilized the following standard criteria: ICC < 0.5: poor reliability; 0.5 ≤ ICC < 0.75: moderate reliability; and ICC ≥ 0.75: good reliability.ResultsA total of 78 men in the prostate arm (38 Butterfly, 40 Clarius) and 45 in the bladder arm (24 Butterfly, 21 Clarius) were randomized and included in this study. The mean prostate volume based on GIm was larger in the Clarius group (p = 0.044). Other baseline characteristics were similar between groups (p > 0.05). The ICCs were 0.78 (95% CI: 0.62, 0.88) and 0.71 (95% CI: 0.51, 0.83) for the Butterfly and Clarius probes, respectively. Regarding bladder volumetrics, the ICCs were 0.82 (95% CI: 0.19, 0.95), 0.72 (95% CI: 0.44, 0.88), and 0.69 (95% CI: 0.13, 0.87) for the Butterfly, Clarius, and bladder scanner, respectively.ConclusionsThe Butterfly iQ demonstrated good reliability for PGV and voided volume measurements, in comparison to moderate reliability for Clarius C3.